Desigualdades entre escolas rurais e urbanas: análise do período 2000 - 2015 - Lira, Lívia Julyana Gomes Vasconcelos (2017)
In a time when indicators point to the improvement of education in Brazil, rural areas face the risk of extinction of their schools. According to the School Census of Basic Education, the year 2014, more than ten thousand rural schools were closed in Brazil from 2010 to 2014. In many regions, the solution to the problems of Education in rural areas is the closure of schools to open others in places with better infrastructure. It is believed, however, that the solution is not the geographical transfer of schools, since rural children and young people need to be educated in their environment. It is necessary to think about what type of education the rural school should offer, inserting in this context the right to a school with basic sanitation, good teachers, classrooms, libraries, computer equipment and sports. It is believed that one of the ways in this direction is to reduce the asymmetries between rural and urban schools, respecting the differences between the two. A starting point for this is to know what these asymmetries are, what their behavior in recent years, how they are distributed throughout the Brazilian Territory, what its determinants and what measures were adopted to reduce them, within the scope of public policies. These were the guiding elements of this dissertation, whose general objective was to identify the asymmetries between urban and rural schools in Brazil from 2000 to 2015. The secondary data used in the study had a five-year periodicity and a state geographic scale. The asymmetries between rural and urban schools were analyzed in four dimensions: infrastructure of basic services, physical infrastructure, availability of equipment and training of teachers and students. In order to rank the federative units regarding the asymmetries studied, the Inequality Index between Rural and Urban Schools (IDERU) was created. The main results of the study showed that, although asymmetries have been reduced from 2000 to 2015, there are still high inequalities, especially in the northern states. Considering the year 2015 and Brazil as a whole, the greatest asymmetries are in the physical infrastructure dimension, more specifically in the proportion of schools with a science laboratory and the proportion of schools with electric energy. It should be noted, however, that the asymmetries in each federative unit are defined by different indicators, which requires specific measures. By identifying the main asymmetries between rural and urban schools, it was possible to perceive that educational public policies, even those aimed at the rural population, do not turn to the creation of a less unequal environment between the countryside and the city. In this sense, the study can be recognized as a useful subsidy in the formulation of educational interventions.